THE ROLE OF COMMITMENT AND TRUST TOWARDS ONLINE LOYALTY IN THE BANKING INDUSTRY (Journal of Business Management and Accounting, 2021)
The purpose of this paper is to determine the influence of online commitment and trust on online loyalty among internet banking users in Malaysia. An intercept survey was conducted among the major banks in the Northern region in Malaysia. A total number of 100 questionnaires were completed and further analyzed. A Partial Least Square (PLS) analysis was performed on the data using the SmartPLS software version 3. SmartPLS is commonly used in marketing and social science studies; thus, the software was employed in this study to predict the relationship among all tested variables as well as analyze their reliability and validity. The results of all the relationships were predicted through hypotheses testing. The result revealed that both commitment and trust have a positive and significant influence on online loyalty. This study provides some practical implications that may be relevant, not only to the banking industry, but also to the financial industry.